2017
DOI: 10.1186/s13054-017-1625-1
|View full text |Cite
|
Sign up to set email alerts
|

Decreased cytokine production by mononuclear cells after severe gram-negative infections: early clinical signs and association with final outcome

Abstract: BackgroundFailure of circulating monocytes for adequate cytokine production is a trait of sepsis-induced immunosuppression; however, its duration and association with final outcome are poorly understood.MethodsWe conducted a substudy of a large randomised clinical trial. Peripheral blood mononuclear cells (PBMCs) were isolated within the first 24 h from the onset of systemic inflammatory response syndrome in 95 patients with microbiologically confirmed or clinically suspected gram-negative infections. Isolatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…On day 3, PBMCs were stimulated with LPS and defective levels of TNF-α were detected that persisted till day 10. Day 3 recorded the lowest levels in all three cytokines TNF, IL6, and IL8, and they remained low until day 7 compared to the prior time points, this profile was characteristic of the non-survivors' profile ( 52 ). A step toward standardization was demonstrated by Monneret et al .…”
Section: Introductionmentioning
confidence: 83%
“…On day 3, PBMCs were stimulated with LPS and defective levels of TNF-α were detected that persisted till day 10. Day 3 recorded the lowest levels in all three cytokines TNF, IL6, and IL8, and they remained low until day 7 compared to the prior time points, this profile was characteristic of the non-survivors' profile ( 52 ). A step toward standardization was demonstrated by Monneret et al .…”
Section: Introductionmentioning
confidence: 83%
“…The immunoinflammatory response in critically ill septic patients is very complex with fundamental differences in the host immune response to Gram-positive bacterial pathogens compared with Gram-negative microorganisms [ 31 40 ]. In our previous study [ 41 ], we also demonstrated significant difference in cytokine profile in severe Gram-positive and Gram-negative abdominal sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication from our group we found that failure of adequate production of proinflammatory cytokines by circulating mononuclear cells 48 h after admission for sepsis was interpreted as sustaining the immunosuppression and it was associated with poor outcome. This defective production continued for at least 10 days [ 18 ]. Since CD14 dim /CD16 pos /CD45 pos cells are the monocyte subpopulation providing most of the TNFα production, the low cell count of patrolling monocytes on the third day in nonsurvivors could be associated with the immunosuppression of sepsis.…”
Section: Discussionmentioning
confidence: 99%